Coagulation status after therapeutic plasma exchange using citrate in kidney transplant recipients. Issue 12 (7th September 2016) - Yamada, Chisa; Pipe, Steven W.; Zhao, Lili; Leichtman, Alan B.; Samaniego, Milagros; Sung, Randall S.; Davenport, Robertson D.
Abstract : BACKGROUND: Therapeutic plasma exchange (TPE) is increasingly used for treatment of antibody‐mediated rejection (AMR) after solid organ transplants. There is concern that TPE may increase risk of bleeding, although data are limited. After TPE, clot‐based coagulation tests may not accurately represent the levels of coagulation factors due to the effect of citrate. We investigated protein levels of fibrinogen using antigen detection method (FibAg) and correlated results with a clot‐based fibrinogen activity test (Fib). STUDY DESIGN AND METHODS: Nine kidney transplant recipients who received TPE for AMR were investigated. Fib, FibAg, prothrombin time/international normalized ratio (PT/INR), partial thromboplastin time (PTT), coagulation factor X chromogenic activity (CFX), and ionized calcium (iCa) were measured at pre‐ and post‐TPE and 1, 3, 6, 9, 24, and 48 hours after the first TPE. RESULTS: Mean Fib/FibAg ratio before TPE was 1.08; therefore, all Fib values were normalized (n) by dividing by 1.08. Overall, the mean normalized Fib (nFib)/FibAg ratio at post‐TPE was 0.89 and returned to close to 1.0 at 6 hours after the first TPE. Decreases in nFib, FibAg, and CFX and increases in PT/INR and PTT post‐TPE were observed. The lowest Fib, FibAg, CFX, platelet, and iCa levels were still at levels that would be considered sufficient for hemostasis at all time points. CONCLUSION: The mean nFib/FibAg ratio after TPE was 0.89 and normalized in 6 hours, which demonstrates a persistent effect of citrate for up to 6 hours. Therefore, similar data observed in clot‐based tests of PT/INR and PTT may be falsely elevated up to 6 hours after TPE due to the citrate effect.